2012
DOI: 10.1038/nrgastro.2012.152
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota in IBD

Abstract: IBD-ulcerative colitis and Crohn's disease-is emerging as a worldwide epidemic. An association between the increased incidence of IBD and environmental factors linked to socioeconomic development has been persistently detected in different parts of the world. The lifestyle in developed countries might impair the natural patterns of microbial colonization of the human gut. The interaction of microbes with mucosal immune compartments in the gut seems to have a major role in priming and regulating immunity. In IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
718
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,027 publications
(792 citation statements)
references
References 76 publications
30
718
0
15
Order By: Relevance
“…6 and 7). Inflammation of the digestive tract can disrupt the intestinal cell barrier, thereby increasing the oxygen level in the normally anaerobic intestine 42 and reducing species variety in the gut microbiome 43 . A high-fiber diet might protect against the depletion of positive microbe-microbe interactions caused by the presence of oxygen.…”
Section: Pairwise Interactions Of Modelsmentioning
confidence: 99%
“…6 and 7). Inflammation of the digestive tract can disrupt the intestinal cell barrier, thereby increasing the oxygen level in the normally anaerobic intestine 42 and reducing species variety in the gut microbiome 43 . A high-fiber diet might protect against the depletion of positive microbe-microbe interactions caused by the presence of oxygen.…”
Section: Pairwise Interactions Of Modelsmentioning
confidence: 99%
“…[3][4][5] Most IBD studies have focused on luminal/fecal bacteria, instead of bacterial communities adherent to the intestinal mucosa, 6,7 although the mucosal microbiota are in closer proximity to immune cells. 8 Although the luminal microbiota may simply be a numerical transformation of the mucosal microbiome, 9 comparisons of mucosal and fecal samples have shown that these 2 intestinal compartments have significantly different microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Children with IBD have been reported to have an altered gut microbiome compared with those without the disease, although it is not known for certain if the altered microbiome is causative of the disease [60]. The association of dysbiosis, including abnormal microbiota and, in particular, a reduced complexity of the gut microbial ecosystem, appears to be a hallmark of IBD [61]. Gut microbiota are not the only microbial factor.…”
Section: The Infant Microbiome In Immune Development and Diseasementioning
confidence: 99%